HlyB-dependent secretion of hemolysin by uropathogenic Escherichia coli requires conserved sequences flanking the chromosomal hly determinant. - Cross, M A (1990)
The synthesis and secretion of hemolysin (HlyA) by Escherichia coli are governed by four contiguous genes (hlyCABD) that are closely conserved on plasmids and, among human pathogenic strains, on the chromosome. We have previously shown that in plasmid pHly152 the coexpressed synthesis and export functions are uncoupled by intraoperon transcription termination, which is in turn alleviated by antitermination dictated in cis by a region upstream of the hly operon. In this study we describe an analogous region of ca. 1,100 base pairs flanking the chromosomal hly determinant of the uropathogenic strain E. coli 2001. This region had no significant effect on intracellular levels of hemolysin but activated strongly, both in cis and in trans, the specific hlyB-hlyD-dependent hemolysin secretion function. The secretion-activating region increased the transcription of the secretion gene hlyB, but the transcription effect was not as pronounced as that seen in the pHly152 determinant and was not evident when the region was present in trans to the hemolysin genes, suggesting that, in addition to transcriptional activation, the region may possibly exert a secondary posttranscriptional influence. Southern hybridizations with the 1,100-base pairs secretion-activating sequence showed low identity to plasmid pHly152 and no identity with total DNA from nonhemolytic uropathogenic E. coli or hemolytic isolates of Proteus vulgaris, Proteus mirabilis, and Morganella morganii. In contrast, hybridization to total DNA from hemolytic E. coli isolates belonging to different serotypes showed strong conservation of the activating sequence, indicating that it is an integral component of the chromosomal hly determinant that is widespread among uropathogenic E. coli.